Control efficiency of avermectin and jinggangmycin mixture on major rice diseases and pests - SHAO Meihong; CHENG Chu; KE Hanyun; HUANG Shiwen; LI Chunshou (浙江大学学报. 农业与生命科学版, 2024)
With the continuous advancement of ecological and green agricultural construction, environmentally friendly and low-toxicity biopesticides have been widely developed and utilized. This study investigated the control efficiencies of different active ingredient dosages of avermectin and jinggangmycin (A&J) mixture on major rice diseases and pests via both laboratory tests and field tests. The results revealed significant synergistic effects of the A&J mixture on killing Rhizoctonia solani Kühn, rice planthoppers (Sogatella furcifera and Nilaparvata lugens), Chilo suppressalis, Tryporyza incertulas and Nephotettix bipunctatus. This synergism can partially neutralize the resistance of pathogenic fungus and pests, thereby prolonging the duration of pesticide use. The toxic effects of the A&J mixture on Cnaphalocrocis medinalis and Naranga aenescens were found to be similar to those of avermectin alone. Therefore, the A&J mixture has the potential to improve the prevention and control capacities to major rice diseases and pests, and it is a green prevention and control method that is worthy of widespread promotion and application.